(untitled) (Universal International Scientific Journal, 2026)
This article is devoted to the analysis of the impact of digital management and information systems on financial efficiency in higher education institutions. The study examined the role of ERP, MIS, BI and blockchain technologies in budget planning, financial monitoring and performance-based financing (PBF) mechanisms. Analysis of international experience has shown that digital management systems accelerate accounting processes, reduce budget errors and increase financial transparency. It was found that BI platforms provide real-time analysis and forecasting, and serve for automatic and objective assessment of PBF indicators. In countries with a high level of digital integration, financial efficiency and audit efficiency have increased significantly. The results of the study justify the need to introduce unified financial management information systems in the higher education system of Uzbekistan